2020
DOI: 10.21608/assjm.2020.124644
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Yield Components Assessment of Some Bread Wheat Genotypes

Abstract: This study was conducted at Sakha Agricultural Research Station, ARC, Egypt, during 2018/2019 and 2019/2020 seasons, to evaluate quality and kernels yield components of some local wheat genotypes. In this study, seven bread wheat cultivars (Misr1, Misr2, Gemmiza11, Shandaweel1, Sakha95, Misr3, and Giza171) and 12 wheat lines have been used. The research has been established as a completely randomize design with three replicates. Genotypes had highly significant effects on quality and yield components traits. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This trend is supported by findings from Mahgoub (1987), indicating a decrease in nitrogen recovery with higher fertilizer nitrogen levels. In contrast, Shafshak et al (1994) reported an increase in nitrogen recovery with rising nitrogen levels, while Nofal (1999) noted a slight reduction in nitrogen recovery as nitrogen levels increased.…”
Section: Nitrogen Recovery (Nrc)mentioning
confidence: 96%
See 1 more Smart Citation
“…This trend is supported by findings from Mahgoub (1987), indicating a decrease in nitrogen recovery with higher fertilizer nitrogen levels. In contrast, Shafshak et al (1994) reported an increase in nitrogen recovery with rising nitrogen levels, while Nofal (1999) noted a slight reduction in nitrogen recovery as nitrogen levels increased.…”
Section: Nitrogen Recovery (Nrc)mentioning
confidence: 96%
“…It could be concluded from these results that to obtain the high grain yield in sandy soils, N level must be increased up to 90-135 kg N/fad. Different studies have reported varying effects of nitrogen levels on NUE; for instance, Sisson et al (1991) noted a decrease in NUE with increasing nitrogen levels, while Compbell et al (1993) and Shafshak et al (1994) found that NUE increased with higher nitrogen fertilizer levels. Additionally, Moll et al (1982) observed a range of 20-32 kg grain per one kg of soil nitrogen when 225 kg N/ha was applied (Gheith et al, 2022).…”
Section: Nitrogen Use Efficiency (Nue)mentioning
confidence: 99%